280 THE PHLAME STUDY: SHORT-TERM ECONOMIC IMPACT OF HEALTH PROMOTION. (1st January 2005) - Kuehl, K. S.; Elliot, D. L.; Goldberg, L.; Moe, E.
Abstract : Purpose: As expenditures on health in the U.S. now exceed $1 trillion for the first time, public and private health care decision makers have called for more rigorous use of economic evaluations to guide resource allocation and spending. Having previously established the benefits of a worksite health promotion intervention on nutrition and exercise behaviors (PHLAME study), the purpose of this study was to compare injury rates and health care costs of two health behavior change strategies among firefighters. Methods: Six hundred eighty seven firefighters participating in the PHLAME program were randomized to a team-centered, group-based educational intervention, a one-on-one, individualized counseling intervention, or a control group. We assessed firefighter's knowledge and behaviors using a questionnaire with established indices. For self-reported injury data, we asked what was the total number of days off work due to injuries in the past year. The economic analysis included frequency distributions of injury and disability claims. We analyzed total healthcare costs associated with individual injuries, missed days of work, and disability claims prior to, during, and after the intervention from 1998 - 2003. Results: There was a 35% reduction in self-reported days off due to injuries among the two intervention groups (team-based approach or individualized counseling) as compared to the control group. Likewise, there was a 57% reduction in number of "reportable injuries" two years after the PHLAME intervention. Total health care costs for injury and disability claims were reduced by over 50% as compared to the pre-intervention costs. The cost of implementation of the health promotion intervention was substantially less in the team-based, group model versus the one-on-one counseling strategy model. Conclusion: The PHLAME intervention reduced injury rates and healthcare costs among fire bureaus. Our findings suggest that a team-based/group intervention has lower costs of administration and implementation than an individualized counseling intervention with similar results among firefighters. Similar team-based formats and health education curriculums could be adapted for other worksite settings and may provide a feasible and cost-effective means for health promotion.